2018
DOI: 10.1111/cod.12951
|View full text |Cite
|
Sign up to set email alerts
|

Different concentrations and volumes of p‐phenylenediamine in pet. (equivalent doses) are associated with similar patch test outcomes: a pilot study

Abstract: The 88% concordance suggests that dose per unit area is more important in determining reactions to allergens than the excipient volume dispensed. Patch testing with a smaller volume of 1% PPD may be a reasonable alternative to testing with 20 mg of 0.3% PPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The elicitation and sensitization capacity depend not only on the concentration, but predominantly on the dose per unit area of allergen delivered to the skin and exposure time 13,21 . In a recent study, good agreement was shown for PPD patch test preparations with equivalent doses of 1.0% and 0.3% pet 22 . If dosed correctly, PPD 1% pet.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The elicitation and sensitization capacity depend not only on the concentration, but predominantly on the dose per unit area of allergen delivered to the skin and exposure time 13,21 . In a recent study, good agreement was shown for PPD patch test preparations with equivalent doses of 1.0% and 0.3% pet 22 . If dosed correctly, PPD 1% pet.…”
Section: Discussionmentioning
confidence: 97%
“… 13 , 21 In a recent study, good agreement was shown for PPD patch test preparations with equivalent doses of 1.0% and 0.3% pet. 22 If dosed correctly, PPD 1% pet. may be safe to patch test with.…”
Section: Discussionmentioning
confidence: 99%
“…Among the three lowest concentrations tested for PPD and PPD-DHC not presented in this In a recent study, good agreement was shown for PPD patch test preparations with equivalent doses of 1.0% and 0.3% pet. 33 If dosed correctly, PPD 1% pet. may be safe to patch test with.…”
Section: Resultsmentioning
confidence: 99%
“…The elicitation and sensitization capacity depend not only on the concentration, but predominantly on the dose per unit area of allergen delivered to the skin and exposure time . In a recent study, good agreement was shown for PPD patch test preparations with equivalent doses of 1.0% and 0.3% pet . If dosed correctly, PPD 1% pet.…”
Section: Discussionmentioning
confidence: 96%